Theoretical aspects of young 6-9 year-old judoists training in sports-health improving groups of a sports school - Khamidullina, G. F.; Latypov, I. K. (The Russian Journal of Physical Education and Sport, 2017)
A long-term sports training is reasonable to consider as a difficult specific system with own typical for it characteristics. The whole process of a long-term sports training includes a lot of variables, that is why, training means and methods undergo great changes. Most authors, studying the system of a long-term sports training, underline the stage of initial training, in particular sports-health improving stage. Material. The article deals with the problem of training judo sports reserve at sports-health improving stage and the possible ways of this problem solution by means of pedagogical technology creation of training young judoists in spots-health improving groups of sports schools. Research methods: scientific literature analysis and summarizing, complex medical check-up of children, conversation, questionnaire survey, anthropometric studies; psychological-pedagogical research (tapping test for the type of central nervous system and temperament determination), experiment. Results. Pedagogical technology of training young judoists in sports-health improving groups of sports school is created. It is based on block- modular system, which helps to select physical training means rationally, as each module is a system of educational-training lessons, which have the unity of content, methodical, organizational, estimating and technological components. During the pedagogical technology creation pedagogical conditions, as one of the components of pedagogical system, were taken into account. These conditions reflect the whole range of educational, material- spatial environment abilities and health protecting pedagogical environment factors. At the same time, pedagogical conditions have a positive influence on personal and procedural aspects, providing effective functioning of young 6-9 year-old judoists training pedagogical technology in sports-health improving groups of a sports school. Conclusion. Pedagogical technology of training young judoists helps to introduce simpler and effective ways of pedagogical aim achievement on the basis of judoists` individual peculiarities.